A Geometric Multiscale modelling approach to the analysis of MSR plant dynamics. (August 2015) - Zanetti, Matteo; Cammi, Antonio; Fiorina, Carlo; Luzzi, Lelio
Abstract: In the framework of the Generation IV International Forum (GIF-IV), six innovative concepts of nuclear reactors have been proposed as suitable to guarantee a safe, sustainable and proliferation resistant source of nuclear energy. Among these reactors, a peculiar role is played by the Molten Salt Reactor (MSR), which is the only one with a liquid and circulating fuel. This feature leads to a complex and highly coupled behaviour, which requires careful investigations, as a consequence of some unusual features like the drift of Delayed Neutron Precursors (DNP) along the primary circuit and heat transfer with a heat-generating fluid. The inherently coupled dynamics of the MSRs asks for innovative approaches to perform reliable transient analyses. The node-wise implicitly-coupled solution of the Partial Differential Equations (PDE) that govern the different phenomena in a reactor would offer in this sense an ideal solution. However, such an approach (hereinafter referred to as Multi-Physics – MP) requires a huge amount of computational power. In this work, we propose and assess a Geometric Multiscale approach on MSR, addressing the core modelling with a 3-D MP approach and the remaining part of the system – e.g., the cooling loop – with simplified 0-D models based on Ordinary Differential Equations (ODE). The aim is to conjugate the accuracy of the MP modelling approach with acceptable computation loads. Reference is made to the Molten Salt Reactor Experiment (MSRE), due to the availability of a detailed design and experimental data that are used for assessment and preliminary validation of the developed simulation tool. Highlights: Multi-Physics Modelling approach to the dynamics of Molten Salt Reactors (MSR). Development of a Geometric Multiscale-based model for the MSR plant dynamics. Assessment of the Geometric Multiscale model against the MSRE experimental data. Transient analysis of graphite-moderated MSRs.